Determination of optimum range for hexavalent chromium Cr(VI) removal using ageratum conyzoide leaf powder (ACLP) - Ezechi, E.H. (American Institute of Physics Inc., 2015)
The optimum range of process parameters for hexavalent chromium Cr(VI) removal were determined in a batch study using Ageratum conyzoide leaf powder (ACLP) as adsorbent. The process parameters were varied in the range 2-10 for Initial solution pH, 135-400 mg/L for initial concentration, 30-180 minutes for contact time and 0.1-0.6 g for adsorbent weight. Solution pH was adjusted using 0.1 M H2S04 and NaOH respectively. Results show that initial solution pH was vital for Cr(VI) removal. At low initial solution pH (pH 2), Cr(VI) removal was high but decreased when the solution was increased from pH 4 to 10. Cr(VI) removal decreased when initial solution concentration was increased and increased when contact time and adsorbent weight was increased. At initial solution concentration of 135 mg/L, residual Cr (VI) concentration was about 53.7 mg/L (61 removal efficiency) at optimum range of pH 2, adsorbent weight 0.3 g and contact time 120 minutes. Ageratum conyzoide leaf powder (ACLP) could be a potential adsorbent for Cr(VI) removal from wastewater. Â© 2015 AIP Publishing LLC.